Sistem Pembiayaan Bank Wakaf Mikro Syariah Dalam Meningkatkan Taraf Ekonomi Nasabah - Ahmad Faisal Hadziq (STAI La Tansa Mashiro, 2020)
Micro Waqf Bank is a pilot project in developing access to financial services in Islamic boarding school environments. The aim of the research is to determine the financing system of the Lan Taburo Islamic Micro Waqf Bank, La Tansa Islamic Boarding School and determine the increase in the economic level of customers in Banjar Irrigation Village, Lebakgedong District after financing from the Lan Taburo Islamic Micro Waqf Bank, La Tansa Islamic Boarding School. This research method uses a qualitative approach with a case study approach. The population in this research are customers who fall into the Halmi I and II classes. Meanwhile, the sample in this study used a purposive sampling technique, namely the head of the kumpi who belonged to the Halmi I and II classes. In collecting data, the techniques used were observation, interviews and triangulation with data analysis using the Miles and Huberman approach. According to the Central Statistics Agency, poverty data in Indonesia reaches 9.78 percent or 26.42 million people of the entire Indonesian population. According to the Central Statistics Agency, poverty data in Lebak Regency reaches 107,930 people out of the entire population of Indonesia. The financing system provided by the Lan Taburo Syariah Micro Waqf Bank to its customers is used as business capital in order to develop the customers' micro businesses as well as the economy of the people of Banjar Irigasi Village, Lebakgedong District, Lebak Regency, this financing adds comfort and increases the spirituality of the workforce even though there is no increase in labor and additional increases in revenue and business profits. The results of this research show that the financing and business assistance system implemented by the Lan Taburo Syariah Micro Waqf Bank has an effect on increasing production/sales, business income, business profits and economic conditions.Keywords: Micro Waqf Bank, qardh financing, business assistance